Stigma, Structure, and Support: A Sociological Exploration of Student Mental Health in Universities. (Journal of Advances and Scholarly Researches in Allied Education, 2026)
University students confront escalating mental health challenges within higher education environments marked by intense academic pressures, financial instability, and cultural expectations of resilience. This paper offers a sociological exploration of "Stigma, Structure, and Support," arguing that mental health issues are not merely individual concerns but products of institutional structures, pervasive stigma, and uneven support systems. It examines how neoliberal university cultures—characterized by performative productivity, hierarchical power dynamics, and commodified well-being—exacerbate distress, particularly among marginalized students facing intersecting inequalities of class, race, gender, and ability.Central to the analysis is the role of stigma in discouraging help-seeking behaviors, fostering identity conflicts, and perpetuating silence around vulnerability. The theoretical framework integrates sociological perspectives on social structure, cultural reproduction, and agency, illuminating pathways from structural barriers to personal experiences. Student-led advocacy emerges as a counterforce, challenging institutional inertia and advocating for holistic support. Ultimately, the paper calls for systemic reforms to destigmatize mental health, redistribute resources equitably, and embed solidarity in university life, promoting mental well-being as a collective responsibility.